2009
DOI: 10.1088/0953-8984/21/17/175408
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transition of ultra thin PrO2films on Si(111)

Abstract: Ultra thin heteroepitaxial PrO(2) films on Si(111) were annealed under UHV conditions and investigated by x-ray diffraction (XRD), x-ray reflectometry (XRR) and spot profile analysis low energy electron diffraction (SPALEED) with regard to structural stability and phase transitions due to the high oxygen mobility of the oxide. This gives information about the manageability of the material and its application as a model catalyst system in surface science. While the samples are stable in UHV at room temperature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
34
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(49 citation statements)
references
References 19 publications
10
34
5
Order By: Relevance
“…We like to mention, that in our previously published XRD experiments on praseodymia films oxidized by molecular oxygen at high pressure, 8,12,20 we observed an oxygendeficient PrO 2− phase. In the light of the praseodymia films oxidized by plasma this phase of the praseodymia films has clearly to be attributed to Pr 6 O 11 .…”
Section: X-ray Diffractionmentioning
confidence: 66%
See 2 more Smart Citations
“…We like to mention, that in our previously published XRD experiments on praseodymia films oxidized by molecular oxygen at high pressure, 8,12,20 we observed an oxygendeficient PrO 2− phase. In the light of the praseodymia films oxidized by plasma this phase of the praseodymia films has clearly to be attributed to Pr 6 O 11 .…”
Section: X-ray Diffractionmentioning
confidence: 66%
“…As discussed before, 8,20,23 the diffraction intensity close to the Si(111) Bragg peak contains the full information about both the vertical lattice constant and the film thickness of the praseodymia films as well as the interface distance and interface roughness due to the interference between substrate and film. Diffraction close to the Si(222) Bragg peak, however, which is forbidden according to kinematic diffraction theory, is only sensitive to the diffraction from the praseodymia film so that this diffraction condition is better suited to characterize quantitatively the praseodymia film itself and to avoid complications with respect to the interference between film and substrate.…”
Section: X-ray Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that after the UHV annealing process the oxide film was reduced to cubic Pr 2 O 3 . 12 In order to keep things simple, we chose the PrO 2 unit cell, which consists of only three atoms, to simulate the oxide layer. The difference to other praseodymia unit cells, e.g., Pr 2 O 3 , is negligible for the simulations shown in this work.…”
Section: Example Of Application: Praseodymium Oxide On Si(111)mentioning
confidence: 99%
“…In order to keep things simple, we will stick with a simple one-column model here because the character of the interface turned out to be identical for both columns in Ref. 12. The first step of our XRD interface analysis is to reduce the amount of free parameters by incorporating XRD analysis results of the measurements at L Ϸ 2, where no significant interference between oxide and film occurs because the intensity of the symmetry forbidden Si͑002͒ S is very weak.…”
Section: Example Of Application: Praseodymium Oxide On Si(111)mentioning
confidence: 99%